Developmental pathway from child maltreatment to children’s bullying: sex difference in the longitudinal dual-process model of self-esteem and depression - Duan, Xiangfei; Zhang, Xianglan; Song, Yanxin (Frontiers in Psychology, 2025)
BackgroundBullying is potentially linked to childhood maltreatment, yet distinctions among maltreatment types and their underlying mechanisms remain under-examined.ObjectiveThis study tested whether emotional and physical maltreatment predict children’s bullying perpetration through self-esteem and depressive symptoms, and whether these indirect pathways differ by gender.MethodIn a three-wave longitudinal design spanning approximately 12 months, data were collected at baseline (T1, mid-December, n = 780), 6-month follow-up (T2, mid-June, n = 774), and 12-month follow-up (T3, mid-December, n = 706). Mediation models examined self-esteem and depression as parallel mediators between emotional/physical maltreatment (T1) and bullying (T3). Multi-group analyses and Wald tests compared path coefficients and indirect effects across boys and girls.ResultsLongitudinal mediation revealed that the indirect effect of T1 emotional maltreatment on T3 bullying via T2 self-esteem (full mediation, βboys = 0.017, SE boys = 0.008, 95% CI [0.002, 0.032]) and the indirect effect of T1 physical maltreatment on T3 bullying via T2 depression (partial mediation, βboys = 0.029, SE boys = 0.013, 95% CI [0.005, 0.053]) were significant only among boys.ConclusionThe finding that distinct maltreatment types are linked to bullying through different, gender-specific psychological pathways highlights the need for tailored prevention strategies that account for both maltreatment type and gender.